Unleashing Creativity And Ambidexterity: How Knowledge Sharing Boosts SME Performance - Nur, Sofyan Ashari; Sadewo, Satrio Tegar (JURNAL MANAJEMEN DAN BISNIS, 2025)
This study investigates the direct impact of employee creativity and organizational ambidexterity on the performance of SMEs operating in the creative industry in Yogyakarta, Indonesia. It also explores the moderating role of knowledge sharing in these relationships. Employing a quantitative approach, data were collected from 170 SME managers selected through purposive sampling. Structural Equation Modeling (SEM) using SmartPLS software was utilized for data analysis. The findings reveal that both employee creativity and ambidexterity significantly and positively influence SME performance, underscoring their strategic importance in dynamic and innovation-driven sectors. Moreover, the study highlights that knowledge sharing plays a significant moderating role in strengthening the relationship between employee creativity and SME performance. This suggests that when creative contributions are supported by a strong culture of knowledge exchange, performance outcomes are amplified. However, the moderation effect of knowledge sharing is not evident in the relationship between ambidexterity and performance. This indicates that the benefits of ambidexterity may operate independently of knowledge sharing mechanisms, potentially relying more on strategic alignment and organizational structure. Overall, the study contributes to a deeper understanding of how internal capabilities and knowledge dynamics interact to drive SME success, offering practical implications for capability development in creative industries.